Gender gap in Japan’s labor market : trends, policies, and implications - Mariňaková, Alica; Stuchlíková, Zuzana, 1979-; Pantea, Smaranda; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis examines the effectiveness of Japanese government policies in reducing gender disparities in the labor market between 2000 and 2023. Despite Japan's status as a developed economy, persistent gender inequalities remain, hindering both economic growth and social equity. This thesis employs a mixed-methods approach, combining quantitative analysis of labor market trends with a qualitative assessment of key policy frameworks, including the Equal Employment Opportunity Act, the Act on Promotion of Women’s Participation and Advancement in the Workplace, and the “Womenomics” initiative. The analysis reveals that while Japan has made progress in shrinking the gender gap, substantial wage gaps, underrepresentation in leadership roles, and occupational segregation continue to disadvantage women. The thesis evaluates Japan’s policies against international frameworks and recommendations, highlighting limitations in enforceability, accountability, and the lack of effective mechanisms to challenge deeply rooted social norms. A comparative case study of Iceland highlights the potential impact of binding and more enforceable policies. Finally, regression analysis indicates that gender wage gaps are negatively correlated with GDP growth and labor productivity. The findings underscore the need for more transformative that tackle structural barriers and promote genuine gender equality in Japan’s labor market.
Vedoucí práce: Zuzana Stuchlíková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses